2021
DOI: 10.3389/fcvm.2021.736497
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Gene Expression Profiling Analysis Reveals Potential Molecular Mechanisms and Candidate Biomarkers for Early Risk Stratification and Prediction of STEMI and Post-STEMI Heart Failure Patients

Abstract: Objective: To explore the molecular mechanism and search for the candidate differentially expressed genes (DEGs) with the predictive and prognostic potentiality that is detectable in the whole blood of patients with ST-segment elevation (STEMI) and those with post-STEMI HF.Methods: In this study, we downloaded GSE60993, GSE61144, GSE66360, and GSE59867 datasets from the NCBI-GEO database. DEGs of the datasets were investigated using R. Gene ontology (GO) and pathway enrichment were performed via ClueGO, CluePe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…A binomial distribution variable was then used in the LASSO classification, as well as the 1 standard error of the minimum criteria (the 1-SE criteria) lambda value used to build the model with good performance but the least number of variables for 10-fold cross-validation. AUC values were used to evaluate the model's ability to differentiate between DCM and normal samples by the pROC package in R (13,14). The data analysis process is depicted in Figure 1.…”
Section: Logistic Regression Modelmentioning
confidence: 99%
“…A binomial distribution variable was then used in the LASSO classification, as well as the 1 standard error of the minimum criteria (the 1-SE criteria) lambda value used to build the model with good performance but the least number of variables for 10-fold cross-validation. AUC values were used to evaluate the model's ability to differentiate between DCM and normal samples by the pROC package in R (13,14). The data analysis process is depicted in Figure 1.…”
Section: Logistic Regression Modelmentioning
confidence: 99%
“…This is consistent with the results we obtained in the ssGSEA single-gene association test. While NFIL3 ( 38 ) and MCEMP1 ( 39 ) currently with only a few omics studies demonstrated their potential relationship with AMI, our study points to the potential clinical value of both, which may be a viable direction for future research. It is worth noting that the expression levels of these key genes were verified by qRT-PCR, and the results were consistent with the results of bioinformatics.…”
Section: Discussionmentioning
confidence: 74%
“…A recent study proposed the diagnostic value of a combination of five genes identified by logistic LASSO regression to discriminate STEMI patients from controls and nominated two genes as predictive biomarkers of post-STEMI HF. However, the robustness of this conclusion could be challenged by the heterogeneity of the sample source [ 25 ]. Another three-gene model for recognizing post-acute MI HF [ 30 ] suffered from data reuse and lack of validation, significantly impacting the generalizability.…”
Section: Discussionmentioning
confidence: 99%